2016
DOI: 10.1016/j.bbagen.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

A novel chemically modified analogue of xenin-25 exhibits improved glucose-lowering and insulin-releasing properties

Abstract: Glutamine (gln)-modified analogues of xenin may represent an attractive therapeutic approach for type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…A follow‐up study employing chronic administration of xenin‐25[Lys 13 PAL] to high fat fed diabetic mice confirmed this suggestion, as treated mice presented with augmented insulin secretion, improved glucose homeostasis, enhanced tissue insulin sensitivity, and partial restoration of normal islet morphology . Moreover, knowledge that serine‐like proteases are primarily responsible for xenin‐25 degradation, led to the generation of a modified xenin‐25 analogue where Lysine (Lys) and Arginine (Arg) amino acid residues were substituted for Glutamine (Gln), to yield xenin‐25‐Gln (Table ) . Xenin‐25‐Gln was enzyme resistant and retained biological activity, with chronic administration in high fat fed and ob/ob mice resulting in enhanced metabolic control, increased GIP sensitivity, and improved circulating lipid profile .…”
Section: Xenin‐25 As An Antidiabetic Agentmentioning
confidence: 90%
See 1 more Smart Citation
“…A follow‐up study employing chronic administration of xenin‐25[Lys 13 PAL] to high fat fed diabetic mice confirmed this suggestion, as treated mice presented with augmented insulin secretion, improved glucose homeostasis, enhanced tissue insulin sensitivity, and partial restoration of normal islet morphology . Moreover, knowledge that serine‐like proteases are primarily responsible for xenin‐25 degradation, led to the generation of a modified xenin‐25 analogue where Lysine (Lys) and Arginine (Arg) amino acid residues were substituted for Glutamine (Gln), to yield xenin‐25‐Gln (Table ) . Xenin‐25‐Gln was enzyme resistant and retained biological activity, with chronic administration in high fat fed and ob/ob mice resulting in enhanced metabolic control, increased GIP sensitivity, and improved circulating lipid profile .…”
Section: Xenin‐25 As An Antidiabetic Agentmentioning
confidence: 90%
“…More recent research has highlighted the potential of xenin‐25 as a direct independent insulinotropic agent, along with an ability to potentiate the insulin‐releasing and glucose‐lowering effects of the incretin hormone, glucose‐dependent insulinotropic peptide (GIP) . Furthermore, related studies have revealed that xenin‐25 enhances pancreatic beta‐cell proliferation in both rodent and human beta‐cells (Figure ) .…”
Section: Biological Activity Of Xenin‐25mentioning
confidence: 99%
“…After the 28‐day treatment period, glucose tolerance (18 mmol/kg body weight; i.p. and oral) and metabolic response to feeding, were examined in overnight (12 hours) fasted lean and DIO mice treated with either peptides or saline as described previously . Whole‐body insulin sensitivity tests (25 U/kg body weight) were carried out as described previously using fed mice …”
Section: Methodsmentioning
confidence: 99%
“…Another gut hormone, Xenin‐25, is secreted by K cells in the small intestine following nutrient ingestion and acts through neurotensin receptor 1 (NTR1) . Building on previous research, generation of a stable xenin‐25 mimetic, Xenin‐25[Lys(13)PAL], with potent anti‐diabetic efficacy has been achieved . NTR1 is expressed throughout the brain, particularly in the hippocampus and entorhinal cortex .…”
Section: Introductionmentioning
confidence: 99%
“…19 Building on previous research, generation of a stable xenin-25 mimetic, Xenin-25[Lys (13)PAL], with potent anti-diabetic efficacy has been achieved. 20 NTR1 is expressed throughout the brain, 21 particularly in the hippocampus and entorhinal cortex. 22 Mutations in the NTR1 gene are associated with impaired working memory in humans 23 and antagonism of NTR1 impairs spatial learning.…”
mentioning
confidence: 99%